Jovens estudantes do ensino médio integrado no Instituto Federal de Salto: experiências do presente e projetos de futuro - Oliveira, Caíque Diogo de (Universidade Federal de São Carlos, 2019)
This dissertation aims to understand the meanings that the young high school students integrated in the IFSP Campus Salto assign to the school experience in integrated high school and their future projects after completing basic education, giving visibility to gender asymmetries, and, where relevant, color / race inequalities. We carried out a study that included the application of a survey with open and closed questions to the 191 students of the intermediate level courses integrated in industrial automation and informatics in the 1st, 2nd and 3rd years. The results analysis was performed primarily quantitatively and secondarily qualitatively, counting on the support of the likert scale for the quantification of the elements inherent to the school experience. We found that there is a predominance of males versus females in integrated middling courses. The school has a representative "color / race", according to the method used by IBGE, similar to the locality where it is inserted. These youngsters seek the integrated high school of the federal school because they believe that the school will provide quality teaching, with better teachers, increasing the possibilities of continuing the studies and of insertion qualified in the job market. Although integrated secondary education courses are, at the documentary level, justified by the regional demand for the training of workers, we have identified that the meanings that these young people attribute to vocational education indicate that the integrated secondary education of the IFSP campus Salto goes far beyond professionalization and attendance of local economic demands, being constituted as a space of formation with qualified teachers and of integration between the students. Regarding professional education, the study points out that some of the assumptions about the professionalization of young people through the "flexibilization" of school curricula that underpinned the reform of secondary education proposed by Law 13.415 / 2017 do not apply what was found among adolescents in this research , since the participants of the research affirmed that both the common base subjects and the professional disciplines generally tend to increase students 'interest in continuing their studies and assisting in the elaboration of students' future projects. More specifically in future projects, we realize that, in general, the expectation of these / these young people is to attend higher education after the end of high school, however, a generalized analysis shows that the sexual division of labor present in modern society manifests itself in the field of possibilities of these investigated youngsters, since, while the students are in search of careers related to the technical courses, the students have a greater variety of professions in your answers.
Young high school students integrated in the Federal Institute of Salto: present experiences and future projects
Keywords: Juventude; Educação técnica; Trabalho; Gênero; Projetos de futuro; CIENCIAS HUMANAS::EDUCACAO